Implications of the Constitutional Court Decision on the Authority of the Financial and Development Supervisory Board in Determining State Losses - Ahmad, Asria Wahyuni; Na'a, Mohammad Feir Chalifardy (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This research examines the authority of the Financial and Development Supervisory Board in auditing state financial losses following Constitutional Court Decision Number: 28/PUU-XXIV/2026 in corruption cases, as regulated under Law Number 1 of 2023 concerning the Criminal Code. The decision emphasizes that auditing state losses constitutes the constitutional authority of the Supreme Audit Board. Purposes of the Research: This study aims to examine and analyze the legal implications arising from Constitutional Court Decision Number 28/PUU-XXIV/2026 on the authority of Financial and Development Supervisory Board in auditing state financial losses. It focuses on assessing how the decision reshapes institutional roles and affects the legal framework governing the determination of state losses in corruption cases. Methods of the Research: The research employs a normative juridical method (normative law research), which is based on legal norms applicable within society. This approach analyzes statutory regulations, legal principles, and relevant doctrines to understand how legal norms function as guidelines for behavior, particularly in relation to institutional authority in auditing state financial losses. Findings of the Research: The findings show that the Constitutional Court's decision functionally limits the Financial and Development Supervisory Board authority in determining state losses, shifting it to the role of investigating support and initial data provider. However, structural uncertainties have not been fully resolved due to derivative regulations, such as Presidential Regulation Number 192 of 2014, which recognizes that Financial and Development Supervisory Board authority is still in effect without a clear transition mechanism. The novelty of this research lies in an in-depth analysis of the normative void after the Constitutional Court's decision that has not been addressed by implementing regulations, as well as its practical implications for the effectiveness of corruption eradication.